Analisis Kekuatan Struktur Rangka Greenhouse Tipe Single Span Menggunakan Metode Finite Element Analysis - Mas Wisnu Aninditya; Muhammad Salman Fadhil; Kemal Mahfud (Universitas Muhammadiyah Metro, 2026)
The structural integrity of greenhouse facilities is fundamental to agricultural safety and productivity, necessitating rigorous analysis of material stiffness and strength to withstand physical loads. This study evaluates the structural feasibility of a single-span greenhouse frame constructed from galvanized iron, specifically comparing the mechanical performance of a design integrated with